(untitled) (The International Journal of Educational Sciences and Arts, 2025)
This research examines the music and poetic aesthetics in the poetry of Suraqa ibn Mirdas al-Barqi. I relied on a descriptive-analytical approach, which focuses on observing the poet’s aesthetic images and highlighting their beauty, seeking to explore his poetic ability to highlight that beauty. In this study, I drew from a variety of sources, primarily literary books. I mention in the introduction our poet’s collection of poems, followed by "Classes of the Masters of Poets," "The Pillar of the Beauties of Poetry, Its Etiquette, and Its Criticism," and "The Songs," among others. My research was divided into two sections: the first, "Poetic Music," and the second, "Poetic Image," followed by a conclusion.